Weathering and erosion - Maloof, Torrey (Huntington Beach, CA : Teacher Created Materials, 2015)
Earth is constantly changing. Wind, water, and even humans change Earth's surface. The land is broken down and worn away by erosion. The Grand Canyon was made from erosion. Many other landforms were made this way, too.
Ever-changing Earth -- Wind, water, and more -- People play a part -- Seeing is believing -- Let's do science!
Library Media Connection, September 2015
Includes index.
2.1
K-3
Library Media Connection
460L
Keywords: Erosion -- Juvenile literature; Landforms -- Juvenile literature; Erosion; Landforms